5 - Civil Society and the Democratic Experience in Kenya: A Review of Constitution-Making from the Middle: Civil Society and Transition Politics in Kenya, 1992-1997, by Willy Mutunga. Sareat & Mwengo, Nairobi, 1999 - Godwin R. Murunga, (African Sociological Review, 2000)
Abstract